The Internalization of Wasathiyah (Moderation) Values Through Pesantren-Based Education - Ridwan, Ahmad; Mahmudi, Ansor Feri (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2023)
The notion of radicalism and liberalism that widespread in the globalization era make the Islamic boarding schools need to improve the moderate values. The objectives of this research are to explain the teaching, imitation, and the impact of instilling the moderate values through pesantren-based education at PP Hidayatul Mubtadi’ien Ngunut and PP Panggung Tulungagung. The research was field research with qualitative methods. The data collection method was done by interview, observation, and documentation. The results of this research showed that: (1) The internalization through teaching aswaja values, namely tasamuh, tawasuth, tawazun, and amar ma'ruf nahi munkar, in Islamic boarding schools used the method of recitation, lectures, discussion or bahtsul masail as well as using teaching resources and media in the form of turats. (2) The imitation of aswaja values as a method in the internalization stage is done by Kyai, and teachers in daily activities have been taught and exemplified to the students in the form of refraction in the boarding school. (3) The formation of a moderate attitude of santri is the impact of internalizing the values of tasamuh, tawasuth, tawazun and amar ma'ruf nahi munkar, which are internalized in Islamic boarding schools to know who they are by not taking sides with extreme radical or otherwise liberal understandings.